The Impact of Financialization on Innovation in Enterprises--An Empirical Study Based on Chinese A-share Listed Companies - He, Liushuo (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper examines the impact of corporate financialization on the innovation activities of Chinese A-share listed companies. The study finds that a higher degree of corporate financialization is associated with lower levels of innovation, indicating that financialization suppresses corporate innovation. This phenomenon primarily arises because the objective of allocating financial assets is to substitute financial asset income for main business income, leading firms to focus excessively on short-term financial returns rather than long-term physical investments. The study recommends that policymakers focus on the coordinated development of finance and the real economy, while being vigilant against the negative impacts of excessive financialization on high-quality economic growth. Additionally, corporate managers should devise prudent asset allocation strategies to ensure that financial investments support innovative development in the real sector.